Book review: Czarzasty, J., Kliszko, Cz. (eds.), Świat (bez) pracy. Od fordyzmu do czwartej rewolucji przemysłowej. Monografia dedykowana Profesorowi Juliuszowi Gardawskiemu [The world with(out) work. From Fordism to the fourth industrial revolution]. - Sroka, Jacek (Warsaw Forum of Economic Sociology, 2023)
Nowadays, Economy 4.0 is a common metaphor that refers to software development. Along other well-known and newer terms related to work and employment, this metaphor is one of the leading themes of the book edited by Czesława Kliszko and Jan Czarzasty from the College of Socio-Economics at SGH Warsaw School of Economics. This multi-faceted volume that is impressive both with its quality and quantity of papers authored by many researchers, is published in honor of the outstanding Polish researcher, Professor Juliusz Gardawski. A fully accomplished man in a lot of areas, in line with what Abraham Maslow (2006) meant when he wrote about healthy people, i.e. ‘self-actualizing people’ who realize their needs in a harmonious way, in unison and in cooperation with their community, for their own benefit and for the common good. This excellent and meticulously edited book opens with congratulatory letters from the Rector of SGH Warsaw School of Economics, Professor Marek Rocki, and the Dean of the College of Socio-Economics at SGH Warsaw School of Economics, Professor Wojciech Morawski. Notes on Professor Juliusz Gardawski and his accomplishments are expanded in the ‘Preface: on Professor Juliusz Gardawski’. The authors of the ‘Preface…’, Czesława Kliszko and Jan Czarzasty, warmly, aptly and at the same time humorously characterized the life and the academic accomplishments of this known and acclaimed researcher, with the use of many quotes from the authors of papers included in the book.